Philippines : Report on the Observance of Standards and Codes-Fiscal Transparency Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This report provides an assessment of the Observance of Standards and Codes on Fiscal Transparency Module for the Philippines. The Philippines meets the requirements of fiscal transparency in many important respects. Despite broad adherence to the transparency code, there are some key areas that require strengthening. Although the existing responsibilities, procedures, and reporting arrangements are well defined, more efforts are required to enforce them, to clearly define accountabilities, and to take firm and demonstrable corrective action when they are not met.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet